Executive wisdom: a study of phronesis in modern management practice - Steyn, Francois (Graduate School of Business (GSB), 2020)
The prominence of executive management failures brings to the fore concerns with a perceived lack of management scholarship impact. Executive managers should be better prepared for a complex world of work and there is a growing scholarly awareness that this requires more focus on practical knowledge (developed though phronesis), which has largely been ignored in favour of theoretical knowledge (developed through episteme) and specialist craft skills (developed through technê). This thesis contributes to the discourse by analysing phronesis, as the virtue underpinning practical knowledge within the managerial scholarship domain. The thesis highlights the fact that, despite its utility, phronesis is generally absent from management scholarship, from professional development and from executive management practice. A phronesis-infused, practice-focused pedagogy is required. However, given the abstruseness of phronesis as a concept in the executive management context, what should a phronesis-pedagogy entail? How can the progress of executive managers in developing their phronesis be gauged? In seeking answers to these questions, this study crystallises a definition and conceptual typology of managerial phronesis through an inductive Gioia Grounded Theory analysis of relevant literature published over the past decade. Managerial phronesis is defined as a morally-imbued capacity for sense-making and managerial action aimed at virtuous outcomes. It is characterised as a situationally embedded developmental and practical skill characterised by interrelated Modes of Engaging, Knowing and Thinking, Being, and Acting. However, understanding phronesis in the applied executive management context demands that the theory be extended to practice. The theory was therefore tested through a two-phased Qualitative Content Analysis. The first analysis of transcripts of interviews with practicing phronetic social scientists was followed by an analysis of minor dissertations submitted by Executive MBA students from the University of Cape Town’s Graduate School of Business. In this context, Phronetic Social Science embodies phronesis-in-action and the Executive MBA represents a phronetic executive management practice programme. The analysis validated the Grounded Theory typology and extended it by highlighting the existence of “embraces paradox” as a further characteristic of a phronetic Mode of Knowing and Thinking. A credible typology of managerial phronesis emerges from the research. This thesis therefore contributes to the discourse on the training of executive managers. It clarifies how phronesis as a vital managerial competence manifests in practice. In so doing, this research offers the management scholarship discipline a framework for developing good executive managers.